Preparation method of bio-based 1, 5-pentanediol

By using the composite metal nitride catalyst modified by agricultural and forestry waste carbon, the efficient isomerial hydrogenation reaction between tetrahydrofurfuryl alcohol and hydrogen is achieved to generate 1,5-pentanediol, solving the high cost of precious metal catalysts in the prior art and the problem of low efficiency, high-efficiency and low-cost preparation of biobased 1,5-pentanediol is achieved.

CN119320308APending Publication Date: 2025-01-17WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411432907.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the existing synthesis methods of biobased 1,5-pentanediol, the use of noble metal catalysts leads to high production costs and low yields, making it difficult to achieve continuous production and efficient conversion.

Method used

Using composite metal nitrides or oxides based on agricultural and forestry waste carbon as catalysts, 1,5-pentanediol is generated by isomerial hydrogenation reaction of tetrahydrofurfuryl alcohol and hydrogen. The catalyst is composed of metals such as osmium, lanthanum, cerium, etc. The carbon material is combined with carbon and the agricultural and forestry waste carbon is used as a support to improve the surface area and activity of the catalyst through acid treatment and modification treatment.

Benefits of technology

It realizes efficient catalytic reaction under mild conditions, improves the yield and selectivity of 1,5-pentanediol, reduces production costs, and solves the high cost and low efficiency problems of precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005084167910000021
    Figure BDA0005084167910000021
  • Figure BDA0005084167910000041
    Figure BDA0005084167910000041
  • Figure BDA0005084167910000051
    Figure BDA0005084167910000051
Patent Text Reader

Abstract

The invention provides a preparation method of bio-based 1, 5-pentanediol, which comprises the following steps: carrying out isomerization and hydrogenation reaction on raw materials tetrahydrofurfuryl alcohol and hydrogen under the action of a catalyst to obtain 1, 5-pentanediol; wherein the catalyst is a metal supported catalyst. The novel tetrahydrofurfuryl alcohol hydrogenation catalyst provided by the invention has good reaction conversion rate and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyol synthesis, and specifically relates to a method for preparing bio-based 1,5-pentanediol. Background Art

[0002] 1,5-pentanediol is an important organic synthesis intermediate and an important monomer of unsaturated polyester and polyurethane. It can also be used as a green solvent for antifreeze and chemical synthesis. The traditional synthesis method of 1,5-pentanediol is to use the mixed dibasic acid produced as a by-product of synthesizing adipic acid as a raw material, esterify the mixed dibasic acid and methanol to generate a mixed dibasic acid dibasic ester, and then obtain 1,5-pentanediol through a hydrogenation reaction. For example, CN1565728A elaborates on the preparation of 1,5-pentanediol by hydrogenation reaction using dimethyl glutarate as a raw material, and CN114524707A elaborates on the esterification reaction using mixed dibasic acid and higher fatty alcohol as raw materials, and then uses the esterification reaction liquid as a raw material to obtain 1,5-pentanediol in high yield through a hydrogenation reaction. Another synthesis method is to use cyclopentadiene as a raw material, obtain epoxypentenal through oxidation, and then prepare 1,5-pentanediol through a hydrogenation reaction.

[0003] With the promotion of the national carbon reduction policy, biomass has received more and more attention due to its wide sources and large reserves. It is more environmentally friendly to use biomass as the primary raw material to synthesize various chemicals. For the synthesis method of bio-based 1,5-pentanediol, furfural or tetrahydrofurfuryl alcohol is mainly used as raw materials, and 1,5-pentanediol is directly hydrogenated. The catalyst involved is a supported precious metal catalyst, such as one or more of rhodium, rhenium, palladium, iridium, etc. The catalyst is expensive and difficult to recycle, which seriously increases the production cost. Therefore, it is very necessary to develop a low-cost, high-yield bio-based route to efficiently prepare 1,5-pentanediol. Summary of the invention

[0004] The purpose of the present invention is to provide a novel method for preparing bio-based 1,5-pentanediol. The catalyst of the present invention has the advantages of high specific surface area, adjustable carrier acidity, easy availability of raw materials, low cost, and high 1,5-pentanediol reaction yield.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] A method for preparing bio-based 1,5-pentanediol, wherein raw materials tetrahydrofurfuryl alcohol and hydrogen undergo isomerization and hydrogenation reactions under the action of a catalyst to obtain 1,5-pentanediol; wherein the catalyst is a metal-supported catalyst.

[0007] Preferably, the catalyst uses a carbon material as a carrier, and more preferably, the carbon material is agricultural and forestry waste charcoal.

[0008] Preferably, the metal in the catalyst is one or more of osmium, lanthanum, cerium, scandium and the like.

[0009] Further preferably, the catalyst comprises metallic osmium and lanthanum or cerium, wherein the molar ratio of osmium to lanthanum or cerium metal is 1:0.9-1.1.

[0010] The reaction of the present invention is shown as follows:

[0011]

[0012] Preferably, the metal in the catalyst is a metal nitride or a metal oxide, and the total mass content of the metal nitride and the metal oxide in the catalyst is 0.1-3.0%, based on the total mass of the catalyst being 100%.

[0013] Preferably, the total mass content of metal nitride and metal oxide in the catalyst is 0.2-2.0%.

[0014] In the present invention, the agricultural and forestry waste charcoal is the residue of crop waste incineration, preferably the residue of coconut shell incineration, reed, ramie, etc.; preferably, the particle size D50 of the agricultural and forestry waste charcoal is 5-15μm, preferably D50 is 8-12μm.

[0015] In the present invention, the residues formed after intermittent batch incineration are collected by screening and dried in an oven for later use.

[0016] In the present invention, the agricultural and forestry waste charcoal needs to be modified, and the modification needs to be treated with acid at high temperature. The acid used is one or more of phosphoric acid, sulfuric acid, acetic acid, etc., the acid concentration is 20-85wt%, and the treatment temperature is 500-800°C;

[0017] In the present invention, the preparation method of the catalyst comprises the following steps:

[0018] Step 1: Dissolve the soluble metal nitride or metal oxide in acid, then add the carbon material for impregnation. For the acid-insoluble metal nitride or metal oxide, grind it and mix it with the carbon material.

[0019] Step 2: Add KBH4 solution for reduction, centrifuge and dry to obtain the target catalyst.

[0020] In the present invention, the acid in Step 1 is one or more of acetic acid, oxalic acid, hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid, and the immersion time is 1-5 hours, preferably 2-3 hours.

[0021] In step 2, the drying temperature is 80-120° C., and the drying time is 5-10 hours.

[0022] Another object of the present invention is to provide a use of a composite metal nitride catalyst based on agricultural and forestry waste charcoal.

[0023] In the present invention, the treatment amount of the catalyst is 1-10g tetrahydrofurfuryl alcohol solution / (g catalyst·h), preferably 2-5g tetrahydrofurfuryl alcohol solution / (g catalyst·h); the tetrahydrofurfuryl alcohol solution is a tetrahydrofurfuryl alcohol cyclohexane solution with a concentration of 45-48wt%; the reaction pressure is positive pressure, preferably 2-5MPaG, and the molar ratio of hydrogen to tetrahydrofurfuryl alcohol is 10-100:1, preferably 20-40:1;

[0024] Furthermore, the source of the required raw material tetrahydrofurfuryl alcohol is preferably a bio-based source, and the bio-based furfural is hydrogenated to produce tetrahydrofurfuryl alcohol.

[0025] In the present invention, the isomerization and hydrogenation reactions are tetrahydrofurfuryl alcohol isomerization to generate tetrahydro-2H-pyran-2-ol, and tetrahydro-2H-pyran-2-ol hydrogenation reaction to obtain 1,5-pentanediol; and / or the reaction temperature of the isomerization reaction is 80-200° C., preferably 90-150° C.

[0026] Compared with the prior art, the present invention has the following positive effects:

[0027] (1) A new catalyst for catalyzing the reaction of tetrahydrofurfuryl alcohol with hydrogen to prepare 1,5-pentanediol is provided. The catalyst has good stability, high catalytic activity, and can efficiently catalyze the reaction.

[0028] (2) The present invention achieves efficient conversion of bio-based compounds under relatively mild and environmentally friendly conditions, solving the problems in the prior art that 1,5-pentanediol involves precious metal catalysts, cannot be produced continuously, and has low batch reaction efficiency and low yield. DETAILED DESCRIPTION

[0029] The reagents and catalysts used are as follows:

[0030]

[0031]

[0032] Biomass charcoal: Coconut shell burning residues, reed, ramie, etc. are mainly collected from Hainan and Dazhou, Sichuan.

[0033] The test instrument used in this embodiment is:

[0034] The gas chromatography analysis used in the embodiment of the present invention was carried out according to the following method: 30m DB-WAX, ID.: 0.32mm, FD.: 0.25μm; 80-230°C, 3°C / min, nitrogen flow rate: 30mL / min, hydrogen flow rate: 40mL / min, air flow rate: 400mL / min; injection volume: 0.2μL. GC was tested using Agilent7820, and the sample was diluted 3 times with chromatographic methanol.

[0035] Example 1

[0036] (1) Preparation of biochar

[0037] First, the coconut shell residue and other biomass raw materials are first cleaned, ultrasonically cleaned in deionized water at room temperature for 30 minutes, and then dried in an oven at a constant temperature of 90°C for 10 hours. Then, the dried coconut shell residue is mixed with KOH dissolved in a small amount of deionized water at a mass ratio of 1:1, and after being fully stirred for 2 hours, the intermediate product is placed in a vacuum freeze dryer for drying. Using N2 at about 2500cm 3 / min rate to purge the vacuum tube furnace for 10min to ensure that the furnace is in an oxygen-free state, and then put the dried sample into a high-temperature tube furnace, and heat it from room temperature to 800℃ at a heating rate of 10℃ / min. After carbonization for 1h at this temperature, it is gradually cooled to room temperature. The carbonized sample is sieved and immersed in 20% acetic acid for 6h, then filtered and dried. The dried product biochar is then set aside, and the acidity and alkalinity of the biochar are tested using Mettler's acid-base titrator. 0.2g of biochar and 5ml of anhydrous methanol solution are mixed evenly and tested. After testing, the pH value of the biochar is 9.3<pH<12.2.

[0038] (2) Preparation of catalyst: First, 2.22 g of osmium dioxide and 1.54 g of cerium nitride were ground and mixed with 200 g of biochar, and then 103 g of a 20 wt% NaBH4 aqueous solution was added dropwise under stirring. After filtering and washing, the mixture was placed in an oven and dried at 105°C for 12 h to obtain catalyst #A. The mass of the obtained catalyst was 112.7 g, and the composite metal content was about 1.65%.

[0039] (3) Synthesis of 1,5-pentanediol from tetrahydrofurfuryl alcohol: A fixed bed reactor was used for characterization. The fixed bed had a length of 100 cm, an inner diameter of 2.5 cm, a catalyst loading of 20 g, and raw materials and hydrogen were fed from the bottom of the fixed bed. The feed rate of tetrahydrofurfuryl alcohol was 60 g / h, corresponding to a processing capacity of 3 g tetrahydrofurfuryl alcohol / (g catalyst*h). The molar ratio of hydrogen to tetrahydrofurfuryl alcohol was 30:1, the reaction pressure was 3 MPa, and the hot spot temperature was 100°C. After the reaction stabilized, sampling and analysis were performed. The GC analysis results showed that the conversion rate of tetrahydrofurfuryl alcohol to 1,5-pentanediol was 99.5% and the selectivity for 1,5-pentanediol was 92.2% in one-step process.

[0040] Example 2

[0041] (1) Preparation of biochar

[0042] First, the raw material of Phragmites australis was cleaned by ultrasonic cleaning in deionized water at room temperature for 30 minutes, and then dried in an oven at a constant temperature of 90°C for 10 hours. Then, the dried coconut shell residue was mixed with KOH dissolved in a small amount of deionized water at a mass ratio of 1:1, and after being fully stirred for 2 hours, the intermediate product was placed in a vacuum freeze dryer for drying. The mixture was dried by N2 at about 2500cm 3 / min rate to purge the vacuum tube furnace for 10min to ensure that the furnace is in an oxygen-free state, and then put the dried sample into a high-temperature tube furnace, and heat it from room temperature to 700℃ at a heating rate of 10℃ / min, carbonize it at this temperature for 1h, and then gradually cool it to room temperature. The carbonized sample is sieved and immersed in 30% sulfuric acid for 6h, then filtered and dried. The dried product biochar is then set aside, and the acidity and alkalinity of the biochar are tested using Mettler's acid-base titrator. 0.2g of biochar and 5ml of anhydrous methanol solution are mixed evenly and tested. After testing, the pH value of the biochar is 9.3<pH<12.2.

[0043] (2) Preparation of catalyst: First, grind 1.72g cerium oxide and 0.59g scandium nitride and mix them with 200g biochar; then, add 110g of 20wt% NaBH4 aqueous solution under stirring, filter, wash and dry in an oven at 90°C for 10h to obtain catalyst #B. The mass of the obtained catalyst is 98g and the composite metal content is about 1%.

[0044] (3) Synthesis of 1,5-pentanediol from tetrahydrofurfuryl alcohol: A fixed bed reactor was used for characterization. The fixed bed had a length of 100 cm, an inner diameter of 2.5 cm, a catalyst loading of 20 g, and raw materials and hydrogen were fed from the bottom of the fixed bed. The feed rate of tetrahydrofurfuryl alcohol was 40 g / h, corresponding to a processing capacity of 2 g tetrahydrofurfuryl alcohol / (g catalyst*h). The molar ratio of hydrogen to tetrahydrofurfuryl alcohol was 50:1, the reaction pressure was 5 MPa, and the hot spot temperature was 120°C. After the reaction stabilized, sampling and analysis were performed. The GC analysis results showed that the conversion rate of tetrahydrofurfuryl alcohol to 1,5-pentanediol was 98.3% and the selectivity for 1,5-pentanediol was 85.4% in one-step process.

[0045] Example 3

[0046] (1) Preparation of biochar

[0047] First, the ramie biomass raw material was cleaned, ultrasonically cleaned in deionized water at room temperature for 30 minutes, and then dried in an oven at 90°C for 10 hours. Then, the dried coconut shell residue was mixed with KOH dissolved in a small amount of deionized water at a mass ratio of 1:1, and after being fully stirred for 2 hours, the intermediate product was placed in a vacuum freeze dryer for drying. The mixture was dried using N2 at about 2500 cm 3 / min rate to purge the vacuum tube furnace for 10min to ensure that the furnace is in an oxygen-free state, and then put the dried sample into a high-temperature tube furnace, and heat it from room temperature to 600℃ at a heating rate of 10℃ / min, carbonize it at this temperature for 1h, and then gradually cool it to room temperature. The carbonized sample is sieved and immersed in 25% hydrochloric acid for 6h, then filtered and dried. The dried product biochar is then set aside, and the acidity and alkalinity of the biochar are tested using Mettler's acid-base titrator. 0.2g of biochar and 5ml of anhydrous methanol solution are mixed evenly and tested. After testing, the pH value of the biochar is 9.3<pH<12.2.

[0048] (2) Preparation of the catalyst: First, 0.7 g of scandium oxide and 0.78 g of lanthanum nitride were dissolved in 500 g of sulfuric acid, and then 200 g of biochar was added. The mixture was stirred evenly and then soaked for 1.0 h. Then, 140 g of a 20 wt% NaBH4 aqueous solution was added dropwise under stirring. The mixture was filtered and washed, and then dried in an oven at 80°C for 10 h to obtain Catalyst #C. The mass of the obtained catalyst was 135.8 g, and the composite metal content was about 0.58%.

[0049] (3) Synthesis of 1,5-pentanediol from tetrahydrofurfuryl alcohol: A fixed bed reactor was used for characterization. The fixed bed had a length of 100 cm, an inner diameter of 2.5 cm, a catalyst loading of 20 g, and raw materials and hydrogen were fed from the bottom of the fixed bed. The feed rate of tetrahydrofurfuryl alcohol was 100 g / h, corresponding to a processing capacity of 5 g tetrahydrofurfuryl alcohol / (g catalyst*h). The molar ratio of hydrogen to tetrahydrofurfuryl alcohol was 100:1, the reaction pressure was 5 MPa, and the hot spot temperature was 150°C. After the reaction stabilized, sampling and analysis were performed. The GC analysis results showed that the conversion rate of tetrahydrofurfuryl alcohol to 1,5-pentanediol in one step was 97.6%, and the selectivity for 1,5-pentanediol was 88.5%.

[0050] Example 4

[0051] (1) Preparation of biochar

[0052] First, the ramie biomass raw material was cleaned, ultrasonically cleaned in deionized water at room temperature for 30 minutes, and then dried in an oven at 90°C for 10 hours. Then, the dried coconut shell residue was mixed with KOH dissolved in a small amount of deionized water at a mass ratio of 1:1, and after being fully stirred for 2 hours, the intermediate product was placed in a vacuum freeze dryer for drying. The mixture was dried using N2 at about 2500 cm 3 / min rate to purge the vacuum tube furnace for 10min to ensure that the furnace is in an oxygen-free state, and then put the dried sample into a high-temperature tube furnace, and heat it from room temperature to 600℃ at a heating rate of 10℃ / min, carbonize it at this temperature for 1h, and then gradually cool it to room temperature. The carbonized sample is sieved and immersed in 25% hydrochloric acid for 6h, then filtered and dried. The dried product biochar is then set aside, and the acidity and alkalinity of the biochar are tested using Mettler's acid-base titrator. 0.2g of biochar and 5ml of anhydrous methanol solution are mixed evenly and tested. After testing, the pH value of the biochar is 9.3<pH<12.2.

[0053] (2) Preparation of the catalyst: First, 1.63 g of lanthanum oxide and 1.54 g of cerium nitride were dissolved in 500 g of nitric acid, and then 200 g of biochar was added. The mixture was stirred evenly and then soaked for 1.0 h. Then, 160 g of a 20 wt% NaBH4 aqueous solution was added dropwise under stirring. After filtering and washing, the mixture was placed in an oven and dried at 100 °C for 10 h to obtain Catalyst #D. The mass of the obtained catalyst was 132.6 g, and the composite metal content was about 1.4%.

[0054] (3) Synthesis of 1,5-pentanediol from tetrahydrofurfuryl alcohol: A fixed bed reactor was used for characterization. The fixed bed had a length of 100 cm, an inner diameter of 2.5 cm, a catalyst loading of 20 g, and raw materials and hydrogen were fed from the bottom of the fixed bed. The feed rate of tetrahydrofurfuryl alcohol was 160 g / h, corresponding to a processing capacity of 8 g tetrahydrofurfuryl alcohol / (g catalyst*h). The molar ratio of hydrogen to tetrahydrofurfuryl alcohol was 100:1, the reaction pressure was 5 MPa, and the hot spot temperature was 150°C. After the reaction stabilized, sampling and analysis were performed. The GC analysis results showed that the conversion rate of tetrahydrofurfuryl alcohol to 1,5-pentanediol in one step was 95.5%, and the selectivity for 1,5-pentanediol was 89.4%.

[0055] Example 5

[0056] (1) Preparation of biochar

[0057] First, the coconut shell residue and other biomass raw materials are first cleaned, ultrasonically cleaned in deionized water at room temperature for 30 minutes, and then dried in an oven at a constant temperature of 90°C for 10 hours. Then, the dried coconut shell residue is mixed with KOH dissolved in a small amount of deionized water at a mass ratio of 1:1, and after being fully stirred for 2 hours, the intermediate product is placed in a vacuum freeze dryer for drying. Using N2 at about 2500cm 3 / min rate to purge the vacuum tube furnace for 10min to ensure that the furnace is in an oxygen-free state, and then put the dried sample into a high-temperature tube furnace, and heat it from room temperature to 700℃ at a heating rate of 10℃ / min. After carbonization for 1h at this temperature, it is gradually cooled to room temperature. The carbonized sample is sieved and immersed in 40% sulfuric acid for 6h, then filtered and dried. The dried product biochar is then set aside, and the acidity and alkalinity of the biochar are tested using Mettler's acid-base titrator. 0.2g of biochar and 5ml of anhydrous methanol solution are mixed evenly and tested. After testing, the pH value of the biochar is 9.3<pH<12.2.

[0058] (2) Preparation of catalyst: First, 0.222 g of osmium oxide and 0.23 g of lanthanum nitride were ground and mixed with 200 g of biochar, and then 140 g of a 20 wt% NaBH4 aqueous solution was added dropwise under stirring. After filtering and washing, the mixture was placed in an oven and dried at 100°C for 10 h to obtain catalyst #E. The mass of the obtained catalyst was 101.8 g, and the composite metal content was about 0.2%.

[0059] (3) Synthesis of 1,5-pentanediol from tetrahydrofurfuryl alcohol: A fixed bed reactor was used for characterization. The fixed bed had a length of 100 cm, an inner diameter of 2.5 cm, a catalyst loading of 20 g, and raw materials and hydrogen were fed from the bottom of the fixed bed. The feed rate of tetrahydrofurfuryl alcohol was 20 g / h, corresponding to a processing capacity of 1 g tetrahydrofurfuryl alcohol / (g catalyst*h). The molar ratio of hydrogen to tetrahydrofurfuryl alcohol was 100:1, the reaction pressure was 5 MPa, and the hot spot temperature was 150°C. After the reaction stabilized, sampling and analysis were performed. The GC analysis results showed that the conversion rate of tetrahydrofurfuryl alcohol to 1,5-pentanediol in one step was 99.5%, and the selectivity for 1,5-pentanediol was 95.4%.

[0060] Comparative Example 1

[0061] First, the raw material of Phragmites australis was cleaned by ultrasonic cleaning in deionized water at room temperature for 30 minutes, and then dried in an oven at a constant temperature of 90°C for 10 hours. Then, the dried coconut shell residue was mixed with KOH dissolved in a small amount of deionized water at a mass ratio of 1:1, and after being fully stirred for 2 hours, the intermediate product was placed in a vacuum freeze dryer for drying. The mixture was dried by N2 at about 2500cm 3 / min rate to purge the vacuum tube furnace for 10min to ensure that the furnace is in an oxygen-free state, and then put the dried sample into a high-temperature tube furnace, and heat it from room temperature to 700℃ at a heating rate of 10℃ / min. After carbonization for 1h at this temperature, it is gradually cooled to room temperature. The carbonized sample is sieved and immersed in 30% sulfuric acid for 6h, then filtered and dried. The dried product biochar is then set aside, and the acidity and alkalinity of the biochar are tested using Mettler's acid-base titrator. 0.2g of biochar and 5ml of anhydrous methanol solution are mixed evenly and tested. After testing, the pH value of the biochar is 9.3<pH<12.2.

[0062] (2) Preparation of catalyst: First, 1.72 g of cerium oxide and 0.51 g of aluminum nitride were dissolved in 500 g of hydrofluoric acid, and then 200 g of biochar was added. After stirring, the mixture was immersed for 1.0 h. Then, 110 g of a 20 wt% NaBH4 aqueous solution was added dropwise under stirring. After filtering and washing, the mixture was placed in an oven and dried at 90 °C for 10 h to obtain catalyst #F. The mass of the obtained catalyst was 98 g, and the composite metal content was about 1%.

[0063] (3) Synthesis of 1,5-pentanediol from tetrahydrofurfuryl alcohol: A fixed bed reactor was used for characterization. The fixed bed had a length of 100 cm, an inner diameter of 2.5 cm, a catalyst loading of 20 g, and raw materials and hydrogen were fed from the bottom of the fixed bed. The feed rate of tetrahydrofurfuryl alcohol was 40 g / h, corresponding to a processing capacity of 2 g tetrahydrofurfuryl alcohol / (g catalyst*h). The molar ratio of hydrogen to tetrahydrofurfuryl alcohol was 50:1, the reaction pressure was 5 MPa, and the hot spot temperature was 120°C. After the reaction stabilized, sampling and analysis were performed. The GC analysis results showed that the conversion rate of tetrahydrofurfuryl alcohol to 1,5-pentanediol was 78.4% and the selectivity for 1,5-pentanediol was 55.6% in one-step process.

Claims

1. A method for preparing bio-based 1,5-pentanediol, characterized in that: The raw material tetrahydrofurfuryl alcohol and hydrogen undergo isomerization and hydrogenation reactions under the action of a catalyst to obtain 1,5-pentanediol; wherein the catalyst is a metal-supported catalyst.

2. The preparation method according to claim 1, characterized in that: The catalyst is supported by a carbon material, and more preferably, the carbon material is agricultural and forestry waste charcoal; Preferably, the metal in the catalyst is one or more of osmium, lanthanum, cerium and scandium.

3. The preparation method according to claim 1 or 2, characterized in that: The catalyst comprises metal osmium and lanthanum or cerium. Preferably, the molar ratio of osmium to lanthanum or cerium metal is 1:0.9-1.

1.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The metal in the catalyst is a metal nitride or a metal oxide, and the total mass content of the metal nitride and the metal oxide in the catalyst is 0.1-3.0%, based on the total mass of the catalyst as 100%; Preferably, the total mass content of metal nitride and metal oxide in the catalyst is 0.2-2.0%.

5. The preparation method according to claim 2, characterized in that: The agricultural and forestry waste charcoal is the residue of burning crop waste, preferably the residue of burning coconut shell, reed or ramie; preferably, the particle size D50 of the agricultural and forestry waste charcoal is 5-15 μm, preferably D50 is 8-12 μm; Preferably, the agricultural and forestry waste charcoal needs to be modified, and the modification requires high-temperature treatment with acid. The acid used is one or more of phosphoric acid, sulfuric acid, acetic acid, etc. The acid concentration is 20-85wt% and the treatment temperature is 500-800°C.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method of the catalyst comprises the following steps: Step 1: Dissolve the soluble metal nitride or metal oxide in acid, then add the carbon material for impregnation. For the acid-insoluble metal nitride or metal oxide, grind it and mix it with the carbon material. Step 2: Add KBH4 solution for reduction, centrifuge and dry to obtain the target catalyst.

7. The preparation method according to claim 6, characterized in that: The acid in step 1 is one or more of acetic acid, oxalic acid, hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid, and the immersion time is 1-5 hours, preferably 2-3 hours; Preferably, in Step 2, the drying temperature is 80-120° C., and the drying time is 5-10 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The treatment amount of the catalyst is 1-10 g tetrahydrofurfuryl alcohol solution / (g catalyst·h), preferably 2-5 g tetrahydrofurfuryl alcohol solution / (g catalyst·h); Preferably, the tetrahydrofurfuryl alcohol solution is a tetrahydrofurfuryl alcohol cyclohexane solution with a concentration of 45-48 wt %; the reaction pressure is positive pressure, preferably 2-5 MPaG; Preferably, the molar ratio of hydrogen to tetrahydrofurfuryl alcohol is 10 to 100:1, preferably 20 to 40:

1.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The required raw material tetrahydrofurfuryl alcohol is sourced from a bio-based source, and the bio-based furfural is hydrogenated to produce tetrahydrofurfuryl alcohol.

Citation Information

Patent Citations

  • Preparation method of 1, 5-pentanediol

    CN114524707A

  • Catalyst and method for preparing 1,5 pentanediol by hydrogenation of 1,5 dimethyl glutarate

    CN1565728A